Improving Language Ability in Children with Speech Delay Aged 3-4 Years by Utilizing Flashcard Media - Maziyyatus Solehah; Siti Muntomimah; Mochammad Ramli Akbar (Bulletin of Early Childhood, 2024)
Language development is one of the important aspects in supporting the child's development process. Children with good language development according to their age will avoid speech delays. The use of Flashcard media as one of the effective ways to improve the language skills of children who experience Speech Delay at preschool age. This study aims to describe how the use of Flashcard media can improve the language skills of children aged 3-4 years at KB Permata Bunda. This study applies data collection techniques through interviews, observations and documentation. The type of research used is qualitative research with classroom action research methods. Data validity checks were carried out using Patton triangulation which emphasizes the interactive and continuous data analysis process during the study. The location of the study was at KB Permata Bunda with 2 boys aged 3-4 years as research subjects. Data collection by providing interventions before and after the use of Flashcard media in children with Speech Delay. Data analysis in this study used Miles & Huberman. The results of the study showed that the use of Flashcard media can improve speaking skills with increased vocabulary, receptive and expressive language understanding after the use of a Flashcard media.